Sa’o Pusaka Pemersatu Perwujudan Sila Ketiga Pancasila dalam Budaya Ngadha - Betu, Silverius; Azi, Paulus Yanuarius; Tue Ude, Yohanes Capestrano; Limbu, Nataniel Umbu; Bao, Antonia Paulina (Ideas Publishing, 2024)
Ngadha community believes in a relationship between their traditional houses (sa'o), land, and ancestors. Sa'o is a gathering of families symbolizing unity, harmony, and togetherness. This research purpose is to explore the role of sa'o in strengthening the unity and cohesion of Ngadha community. The method used descriptive-qualitative, literature review and interviews. Sa’o as a unifying heirloom must be preserved to maintain the unity and harmony of family. This has impact on greater unity and cohesion, namely Ngada Regency, Province, and Indonesian nation. Living the cultural heritage of sa'o means realizing the third principle of Pancasila: the unity of Indonesia.